Distribution of Indian oil sardine Sardinella longiceps along south-west coast of India - BHARTI, VIVEKANAND; JAYASANKAR, J; SHUKLA, S P; VARGHESE, ELDHO; SATHIANANDAN, T V; GEORGE, GRINSON; KRIPA, V; JAISWAR, A K (The Indian Journal of Animal Sciences, 2019)
Rise in temperature directly affects the poikilothermic aquatic animals such as fishes influencing their population biomass and recruitment. With this perspective, a study on spatial-temporal distribution of Indian oil sardine along south-west coast of India (SW) was conducted by classifying the study area into three strata namely: southern, central and northern region. The data was collected and segregated into three seasons, i.e. pre-monsoon, monsoon and post-monsoon. The trend for sea surface temperature was analyzed and compared among three strata and seasons. The trend of standardized catch per hour for all strata and season was also analyzed, along with observation on gear-wise catch of Indian oil sardine. This study indicates towards latitudinal extension and seasonal changes of Indian oil sardine population, besides changing its distribution into deeper water for avoiding the adverse impact of rising temperature.